Acute inhibition of bacterial growth in coastal seawater amended with crude oils with varied photoreactivities - Headrick, Erika L.; Nigro, Lisa M.; Waidner, Lisa A.; Ederington-Hagy, Melissa; Simmering, Arianna L.; Snyder, Richard A.; Jeffrey, Wade H. (Frontiers in Ecology and Evolution, 2023)
The increased potential for contamination of seawater by crude oils requires studies of bacterial biodegradation potential, but little is known of the differential negative impacts of oils on bacterial growth. No two wells generate chemically identical oils; and importantly, solar exposure of crude oil may differentially affect the bacterial response. This study examined light exposure of six different crude oils, and subsequent microbial responses to altered oils. Marine bacterioplankton heterotrophic activities were measured via 3H-leucine incorporation after the addition of oils’ water accommodated fractions (WAFs) that were created under varied solar conditions. Inhibition of production increased with higher concentrations of WAFs, but dose-response trends varied among the oils. Increased solar exposure during WAF preparation generally led to more inhibition, but trends varied among oils. WAFs were also prepared under different parts of the solar spectrum. Solar-irradiated WAFs resulted in significant but variable acute toxicity versus dark counterparts. Solar-induced toxicity was primarily a result of visible and not ultraviolet light exposure. Results indicate responses to oil spills are highly dependent on the source of the oil and solar conditions at the time and location of the spill. The data presented here demonstrate the importance of photochemical changes and oil source in modulating microbial activity and bioremediation potential.